Effects of Venoconstrictive Thigh Cuffs on Dry Immersion-Induced Ophthalmological Changes - Kermorgant, Marc; Sadegh, Ayria; Geeraerts, Thomas; Varenne, Fanny; Liberto, Jérémy; Roubelat, François-Philippe; Bataille, Noémie; Bareille, Marie-Pierre; Beck, Arnaud; Godard, Brigitte; Golemis, Adrianos; Nasr, Nathalie; et al. (Frontiers in Physiology, 2021)
Neuro-ophthalmological changes named SANS (Spaceflight Associated Neuro-ocular Syndrome) reported after spaceflights are important medical issues. Dry immersion (DI), an analogue to microgravity, rapidly induces a centralization of body fluids, immobilization and hypokinesia similar to that observed during spaceflight. The main objectives of the present study were twofold: 1) to assess the neuro-ophthalmological impact during 5 days of DI and 2) to determine the effects of venoconstrictive thigh cuffs (VTC), used as a countermeasure to limit headward fluid shift, on DI-induced ophthalmological adaptations. 18 healthy male subjects underwent 5 days of DI with or without VTC countermeasures. The subjects were randomly assigned into two groups of 9: a control and cuffs group. Retinal and optic nerve thickness were assessed with spectral-domain optical coherence tomography. Optic nerve sheath diameter (ONSD) was measured by ocular ultrasonography and used to assess indirectly changes in intracranial pressure (ICP). Intraocular pressure (IOP) was assessed by applanation tonometry. A higher thickness of retinal nerve fiber layer in the temporal quadrant was observed after DI. ONSD increased significantly during DI and remained higher during the recovery phase. IOP did not significantly change during and after DI. VTC tended to limit the ONSD enlargement but not the higher thickness of retinal nerve fiber layer induced by DI. These findings suggest that 5 days of DI induced significant ophthalmological changes. VTC was found to dampen the ONSD enlargement induced by DI.